Exit Strategies : Policy Options for Countries Seeking Exchange Rate Flexibility - Eichengreen, Barry; Hamann, A.; Jadresic, Esteban; Otker, Inci. (Washington, D.C. : International Monetary Fund, 1998)
In a world of increasing capital mobility and broadening and more diversified trade, many (but not all) developing and transition economies are likely to find it desirable to move from relatively fixed exchange rate regimes to regimes of greater exchange rate flexibility. This paper suggests why, and considers strategies that countries may consider for such a move. It reinforces this discussion with a review of experience from teh past two decades with alternative exchange rate regimes. The paper also identifies policies that can facilitate the transition to greater exchange rate flexibility for countries that wish to pursue this option.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet